Case report: traumatic tenosynovitis of the tarsal synovial sheath in a Purebred Spanish Hors - Giraldo Botero, Lucas (2020)
The case of a Purebred Spanish Horse (PRE) patient, 4.5-year-old male who comes for consultation due to a historical increase of three months in the tarsal region of the left hind limb is reported. Based on the clinical examination and radiological and ultrasonographic evaluation, it was diagnosed with traumatic tenosynovitis of the tarsal synovial sheath. The horse was treated with intrasynovial application with steroidal anti-inflammatory drugs, atropine sulfate and hyaluronic acid, in addition to synovial lavages with dimethyl sulfoxide (DMSO) at intra-synovial level and physiotherapy based on laser and therapeutic ultrasound. The patient responded satisfactorily to the established treatment.